Penerapan Design Thinking untuk Pengembangan Prototipe Website Komunitas Akademik IS Society UNJANI - Irma Santikarama; Meisya Putri Utami (Jurnal Teknologi Terpadu, 2026)
The current IS Society community website prototype is unable to optimally facilitate cross-cohort interactions and academic documentation. These functional limitations create a significant gap in fulfilling user needs. Therefore, this research applies the Design Thinking methodology to redesign and develop the IS Society academic community website prototype. The Design Thinking process integrates qualitative findings obtained from observations and semi-structured interviews with quantitative data collected through direct testing. The prototype was evaluated by 40 participants using the Maze platform to measure task performance and the System Usability Scale (SUS) questionnaire to assess perceived ease of use. The results indicate an average direct success rate of 94.25% across eight task scenarios, with two scenarios achieving 100% success, and an average SUS score of 87.06, categorized as Excellent. These findings suggest that the prototype offers low cognitive load and efficient navigation. However, some issues remain regarding layout clarity and the visibility of interface elements, which led to user errors in the discussion and profile sections. Recommended improvements include emphasizing the visibility of main buttons, simplifying menu labels and symbols, and adding a short introductory guide for first-time users. Overall, this study demonstrates that the implementation of Design Thinking effectively guides data-driven iteration for the development of academic community websites and provides an evaluation framework that can be replicated in similar contexts.